A bargaining model of tax-push inflation : evidence from a Sargan approach to tax-push inflation in Finland - Asplund, Rita (Economic Planning Centre, 1989)
Concluding remarks (s. 51-53).
Keywords: inflaatio; taloudelliset mallit; tulopolitiikka; verotus